2013
DOI: 10.1044/1092-4388(2012/11-0271)
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Convergence in Spanish–English Bilingual Children With Primary Language Impairment

Abstract: Purpose To examine the degree of convergence in word association responses produced by bilingual children with primary language impairment (PLI) in relation to bilingual age peers. Method Thirty-seven Spanish–English bilingual children with PLI, 37 typically developing (TD) controls, and a normative sample of 112 children produced associations to 24 English and Spanish words. The 5 most frequent responses for each stimulus were identified for the normative sample; then the frequency of occurrence of these fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…This is significant because although the differences ranged from 2 to 7 words depending on grade and language, these 30 words represented those that accounted for 75% of the words children used in their narratives. The difference between children with and without PLI noted in core vocabulary use is consistent with the results reported by Sheng et al (2013) for semantic convergence of word association responses and by Ubels (2012) in Spanish–English bilingual children. The present result, however, contradicts the findings reported by Robillard et al (2014) as they did not observe significant differences between TD and PLI groups of bilingual children core words used by each group of children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is significant because although the differences ranged from 2 to 7 words depending on grade and language, these 30 words represented those that accounted for 75% of the words children used in their narratives. The difference between children with and without PLI noted in core vocabulary use is consistent with the results reported by Sheng et al (2013) for semantic convergence of word association responses and by Ubels (2012) in Spanish–English bilingual children. The present result, however, contradicts the findings reported by Robillard et al (2014) as they did not observe significant differences between TD and PLI groups of bilingual children core words used by each group of children.…”
Section: Discussionsupporting
confidence: 90%
“…Bilingual children with PLI may also have lexical-semantic deficits affecting the acquisition and use of vocabulary (Peña, Iglesias, & Lidz, 2001; Sheng, Peña, Bedore, & Fiestas, 2012; Windsor, Kohnert, Lobitz, & Pham, 2010). They have limited vocabulary and difficulties retrieving previously acquired words in both structured and spontaneous tasks (Kohnert & Kan, 2007; Restrepo & Kruth, 2000; Sheng, Bedore, Peña, & Taliancich-Klinger, 2013). They are also likely to have word-learning deficits and require more frequent and focussed exposures compared to TD peers to acquire new vocabulary (Peña et al, 2001).…”
Section: Linguistic Deficits In Bilingual Children With Plimentioning
confidence: 99%
“…Bilingual children with LI, like their monolingual peers, demonstrate low performance on the repeated associations task relative to their peers matched on age of first experience and amount of use of each language indicated reduced depth of semantic knowledge (Sheng et al . , ). Given the extent of lexical–semantic difficulties, we focus on the utility of a semantic measure (rather than single‐word vocabulary) for diagnostic decision‐making.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies on BLI have focused on grammar (Paradis, 2010; Verhoeven, Steenge, & van Balkom, 2011), but recently studies of lexical abilities in BLI children have been published (Ebert, Pham, & Kohnert, 2014; Sheng, Bedore, Peña, & Taliancich-Klinger, 2013; Sheng et al, 2012). In the studies by Sheng et al (2012) and Sheng et al (2013), BLI children showed less developed lexical organization skills in both their languages compared with bilingual children with typical development. They also displayed poor semantic convergence in comparison with bilingual peers with typical development, that is, the BLI children produced fewer associations that were frequent in the normative sample.…”
Section: Language Impairment In Bilingual Populationsmentioning
confidence: 99%